Metafora dalam ucapan presiden UMNO 2000-2010: kuasa patriotisme dan setia kawan - Jamal Rizal, Razali (2014)
From the perspective of cognitive linguistics, the conceptualization process of idea is known as conceptual metaphor. This process involved certain elements utilized to explain the other elements. It prevailed in a language user's thought and influenced by non-linguistic factors in the communication process. To explain the phenomenon, the researcher analyzed the conceptualization of 'power ".”Patriotism" and "solidarity" presented by three UMNO’s presidents (2000-2010) in their speech texts during the party's general assembly. The objectives of the study are to identify, analyze and classify the metaphors used by the speakers. Based on these objectives, the analyses were focused on the metaphor, the structure and the function of metaphorical expressions used by the speakers in their speech texts. For these particular purposes, the Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980), Critical Metaphor Analysis (CMA) by Charteris-Black (2004, 2005) and Metaphor Structural Analysis (MSA) by Christine Brooke-Rose (1958) were employed as a thereoretical framework for this research. Every metaphorical expression identified was class/led based on types of metaphors. This categorization determined the source domain used by the speakers in explaining the target domain in their speech texts. From the metaphors usage, the speakers used various metaphors to conceptualize the ideas. However, there were three most frequent metaphors used by the speakers to conceptualize the ideas, which were the "act" (27.2%), "war" (8.8%) and "traits" (3.791o) metaphor. From the linguistics structure point of view, the speakers used verbs (66.1%) and nouns (24%) as a basis for constructing a metaphorical expression than other types of words. From the functional point of view, the metaphorical expressions constructed by the speakers were more frequently used as a predicate (41916) and complement (33%) in a sentence. From the analysis, there are similarities among the speakers in metaphorical, structural and functional aspect in the conceptualization process. It also shows that the speakers have a common perspectives and views in illustrating the existence and manifestation of the ideas. This can be attributed to their positions and roles as leaders of an organization as well as the influence from the environment, historical context, current socio-political environment and humanity aspects.